Anthropometric characteristics and motor abilities of young female players in relation to competitive success - Nikolic, I.; Kondric, M.; Hublin, T. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The aim of this research is to establish the correlation between anthropometric characteristics, motor and specific abilities and competitive success. The study included 40 young female table tennis players at the age 11±0.33 with training experience a 3.01±0.91 years. The predictive variables were 15 anthropometric measures, 24 motor tests and 6 specific table tennis tasks. The criterion variable - the competitive success was verified on points won and registered on the Croatian Table Tennis Association ranking lists for categories (cadets and young cadets). The correlation between the predictive variables and competitive successfulness was analysed with the Pearson correlation coefficient. The results show that height, arm length, leg length and biacromial range has a statistical positive correlation with the competitive success. The positive correlation with the competitive success was obtained with 4 agility tests in which the intensive body movement or some parts of the body on a relatively small, limited space has been highlighted, and where the outcome has been connected with fast changes of the movement direction, the explosive power of the leg and the arm, the repetitive strength of the arms and the body, and cardiorespiratory endurance. Significant positive correlation was obtained with all 6 specific table tennis tests. This information can help trainers with talent identification, precise selection of players and planning of the training process. Programmes at this age should be targeted towards those abilities which demonstrate the biggest influence on the competitive success.